2013
DOI: 10.3892/ijo.2013.1855
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intracellular iron metabolism by iron chelation affects chromatin remodeling proteins and corresponding epigenetic modifications in breast cancer cells and increases their sensitivity to chemotherapeutic agents

Abstract: Abstract. Iron plays a vital role in the normal functioning of cells via the regulation of essential cellular metabolic reactions, including several DNA and histone-modifying proteins. The metabolic status of iron and the regulation of epige netic mechanisms are well-balanced and tightly controlled in normal cells; however, in cancer cells these processes are profoundly disturbed. Cancer-related abnormalities in iron metabolism have been corrected through the use of iron-chelating agents, which cause an inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…However, further work is still needed to establish whether E2 treatment precipitates such effects on cancer cells. Should this prove to be the case, high dose E2 treatment could provide an alternative to the problematic employment of iron chelation as an anti-cancer therapy [29][30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further work is still needed to establish whether E2 treatment precipitates such effects on cancer cells. Should this prove to be the case, high dose E2 treatment could provide an alternative to the problematic employment of iron chelation as an anti-cancer therapy [29][30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, upregulated expression of CD71 is considered as a marker of poor prognosis in breast cancer patients [28]. Based on these and other relevant observations, iron chelation therapy has been proposed and tested in various forms of cancer [29][30][31][32][33] with mixed results regarding efficacy [34,35] and side effects [36]. One possible reason for the limited efficacy of iron chelation in cancer is that it mostly targets extracellular iron.…”
Section: Introductionmentioning
confidence: 99%
“…This study suggests that HFE expression could be a potential prognostic marker for tumor progression of HNSCC and that iron depletion may be a treatment option for this type of cancer. Similarly, studies on breast cancer cells indicated that the iron chelator deferoxamine (DFO) increased the sensitivity of these cells to chemotherapeutic agents [61]. …”
Section: Cancer and Ironmentioning
confidence: 99%
“…Iron chelators as anti-cancer agents that may be able to synergize with other cancer therapies show potential to reduce tumor burden (Buss et al, 2003;Kalinowski and Richardson, 2005;Pogribny et al, 2013). However, iron chelators (deferasirox, deferoxamine, and deferiprone) that are currently available for clinical use have limitations such as adverse side effects, short biological half-life, and high cost (Neufeld, 2010).…”
Section: Introductionmentioning
confidence: 98%